Use of Handheld Versus Standard Ultrasound Devices in Ultrasound Rotation at the Emergency Department - Ienghong, Kamonwon; Jumroenketpratheep, Kotchakorn; Tiamkao, Somsak; Apiratwarakul, Korakot (Open Access Macedonian Journal of Medical Sciences, 2021)
BACKGROUND: Recently, handheld ultrasound equipment has come to replace standard machines in the training of emergency medicine residents. However, there have been few studies examining how this change has affected medical education. AIM: We aimed to compare standard and handheld ultrasound machines as educational tools in the emergency medicine residency program. METHODS: A cross-sectional survey of 17 emergency medicine residents at Srinagarind Hospital emergency department were trained to use point-of-care ultrasound and provided with handheld ultrasound devices during their 2-week ultrasound rotations, which took place between July 2019 and May 2020. Participants were given a 25-question survey comparing their learning experiences with standard versus handheld ultrasound machines. Data were analyzed using an independent sample t-test, and p < 0.05 was considered statistically significant. RESULTS: The response rate was 100%. At the baseline survey, most participants rated their learning experience as greater than 4 out of 5 with both ultrasound devices. They rated the learning experience with the handheld device as being more enjoyable and accessible but not to a statistically significant extent. There were also no significant differences in participants’ ratings of image quality or the ease of obtaining images. However, they rated the handheld device as being more useful and convenient (p < 0.001 and 0.034, respectively). CONCLUSIONS: The handheld ultrasound machine is useful in the training of emergency medicine residents. Further studies should be conducted to evaluate residents’ competency in using these devices.